Examining the Efficacy of the Project-Based Learning in Enhancing English-Speaking Skills among Students - Nan Cendikia, Aisy; Apoko, Tri Wintolo (International Journal of Research in Education, 2025)
The purpose of this study is to examine the efficacy of implementing Project-Based Learning (PjBL) as a pedagogical model in improving students' English-speaking skills. This study used a mixed methods approach, combining quantitative and qualitative analysis. The research subjects were divided into two classes: an experimental class and a control class, using a purposive sampling technique. The experimental class used PjBL, while the control class used the conventional learning model. Quantitative data was obtained through pre-test and post-test of speaking ability, then analyzed using the Mann-Whitney U test. Simultaneously, qualitative data were collected through semi-structured interviews to describe students' responses to the implementation of the PjBL. The results showed that PjBL model had a significant impact on students' English-speaking ability than the conventional method. Thus, it is recommended to teachers of English to implementing the PjBL model in teaching English language, especially in improving speaking skills among students.